The role of travel- related aspects in the language tourism experience - Iglesias, Montserrat (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2017)
Language tourism as an educational travel niche and a subtype of cultural tourism is little by little generating interest from academicians. While previous research has focused on the language tourism market system demand and on some aspects relating to the supply, this article explores the language tourism product’s travel components. A taxonomy of such components will be presented and constitutes the conceptual framework of a survey that was conducted in Barcelona (Spain) among 234 international university students between 2015 and 2017. The respondents had a major interest in learning Spanish and getting to know the local culture. They were requested to fill in a structured questionnaire with a combination of open and closed questions to find out different aspects concerning their profile, the opportunities for interacting with local residents, their accommodation, catering, leisure and transport arrangements in Barcelona, and the costs deriving from their academic stay. The results provide an overview of key travel-related features that must be taken into consideration in the conception, staging and evaluation of language tourism experiences.